2021
DOI: 10.21203/rs.3.rs-203954/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomechanical Profile of People with Diabetic Neuropathy Attended in Primary Care In East Paulista, Brazil

Abstract: Diabetic neuropathy is one of the main complications of Diabetes Mellitus, which can lead to loss of protective sensation, motor alteration, in plantar pressure, generating deformities, abnormal gait and mechanical trauma to the feet. OBJECTIVEto evaluate the distribution of plantar pressure, sensory, motor changes and balance in people with peripheral diabetic neuropathy. METHODCross-sectional study conducted with individuals registered in the municipal public health network of a city in the east of São Paulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These results were consistent with the findings of Kankanasamut et al [29], Sartor et al [31], Fayed et al [32], Cerrahoglu et al [33], Jorgetto et al [8], Jiang et al [3], Prokai et al [1], de Oliveira Lima et al [34], and Monterio et al [10]. Kankanasamut et al [29] demonstrated that eight weeks of weight-bearing exercises increases vibration perception.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results were consistent with the findings of Kankanasamut et al [29], Sartor et al [31], Fayed et al [32], Cerrahoglu et al [33], Jorgetto et al [8], Jiang et al [3], Prokai et al [1], de Oliveira Lima et al [34], and Monterio et al [10]. Kankanasamut et al [29] demonstrated that eight weeks of weight-bearing exercises increases vibration perception.…”
Section: Discussionsupporting
confidence: 87%
“…The development of diabetic peripheral neuropathy impairs the integrity of tiny joints and internal muscles of the feet which are the main causes of deformity and high plantar pressures [5][6][7][8][9][10]. Improving the feeling of the soles of the feet and the perception of vibration is one of the changes that have been reported as a result of some exercise activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations